KEPEMIMPINAN PEMBELAJARAN KEPALA SEKOLAH DALAM MENINGKATKAN KARAKTER SISWA - Saddam Ramli (Diklat Review : Jurnal manajemen pendidikan dan pelatihan, 2026)
This research focuses on the study of the principal's instructional leadership in shaping student character at the UPT SMA Negeri 2 Enrekang. The purpose of this study is to describe how the principal's instructional leadership plays a role in shaping student character, as well as to identify supporting and inhibiting factors in its development at the school. The method used is descriptive qualitative, with data collection techniques through interviews, observation, and documentation. Data analysis was carried out through the stages of data reduction, data presentation, and conclusion drawing, while data validity was checked using triangulation techniques. The results of the study indicate that the principal's instructional leadership at the UPT SMA Negeri 2 Enrekang has been implemented well. The principal plays an effective role in managing the learning program to improve the quality of graduates, especially in the formation of student character. This is reflected in student behavior that demonstrates discipline in various situations, religiosity in school activities, resilience and responsibility in learning activities, and a school environment free from bullying. All of this is realized through collaboration between the principal and teachers in providing role models and direct practices that can be emulated by students.